A RETROSPECTIVE STUDY EVALUATING GLYCAEMIC CONTROL AND LIPID PROFILES IN DIABETIC PATIENTS FROM KWAZULU-NATAL, SOUTH AFRICA. - Thembane, Nokukhanya; Madlala, Minenhle (Student's Journal of Health Research Africa, 2023)
Background: This study aimed to investigate the lipid profile of diabetic patients in KwaZulu-Natal (KZN), South Africa, a region with a high burden of diabetes. Dyslipidaemia is a common comorbidity in diabetes and is a major risk factor for cardiovascular disease, which is the leading cause of morbidity and mortality in diabetic patients. Methodology: A total of 160 serum sample data were analyzed from the laboratory information system, including 80 diabetic patients and 80 non-diabetic individuals as controls. Lipid profiles, fasting glucose, and glycosylated haemoglobin levels were measured and compared between the two groups. Descriptive statistics were used to summarize the data, and inferential statistics were used to compare means between groups. Results: The study found that diabetic patients in KZN had significantly higher levels of total cholesterol (TC), triglycerides (TG), and low-density lipoprotein (LDL) cholesterol, and significantly lower levels of high-density lipoprotein (HDL) cholesterol, compared to non-diabetic individuals. The mean TC, TG, LDL, and HDL levels were 5.5 mmol/L, 2.5 mmol/L, 3.5 mmol/L, and 1.0 mmol/L, respectively, in diabetic patients, and 4.4 mmol/L, 1.4 mmol/L, 2.4 mmol/L, and 1.4 mmol/L, respectively, in non-diabetic individuals. Conclusion: The study underscores the importance of early detection and management of lipid abnormalities in diabetic patients in KZN to reduce the risk of cardiovascular disease. The findings have implications for healthcare providers and policymakers in the region who are responsible for addressing the burden of diabetes and its complications. Recommendation: Further studies with larger sample sizes and in different regions of South Africa are needed to investigate the prevalence of dyslipidaemia and poor glycaemic control in diabetic patients. Such studies can inform the development of tailored interventions to improve cardiovascular outcomes in diabetic patients in South Africa and other regions of the world with a high burden of diabetes.